The (Ironic) Dove Effect: Use of Acceptance Cues for Larger Body Types Increases Unhealthy Behaviors. (April 2016) - Lin, Lily; McFerran, Brent
The average weight of the population has risen rapidly in much of the world. Concurrently, in recent years, advertisers have begun using larger models in their campaigns, and many of these advertisements claim that their larger models (vs. the thin models commonly used) possess "realistic" body types. Many groups have lauded these moves as beneficial for promoting a healthy body image in society. However, in five studies, the authors find that cues suggesting the acceptance of larger body types result in greater intended or actual consumption of food and a reduced motivation to engage in a healthier lifestyle. The authors suggest that the reason being larger bodied appears to be contagious is that, because it is considered more socially permissible, people exhibit lower motivation to engage in healthy behaviors and consume greater portions of unhealthy food. The authors also contrast acceptance with communications stigmatizing various body types and identify limitations of both approaches. They conclude with implications for public policy.